Urgensi Penanaman Nilai Nilai Anti Korupsi melalui Pendidikan - Siti Alfiyah; Syaiful Anwar; Rifda El Fiah (CV. Creative Tugu Pena, 2024)
The eradication of corruption in Indonesia is still not implemented optimally and still prioritizes prosecution/suppression of corruption cases that occur. The implementation of these efforts is less effective in eradicating corruption because corruption is ingrained in the legal culture of society. This research analyze the urgency of instilling anti-corruption values ​​through education. One way that can be implemented in efforts to eradicate corruption is to prevent corruption which can be done by providing anti-corruption education, especially for students at the basic education level. Basic education is the focus of providing anti-corruption education because it is at this level that a person's character is formed, and anti-corruption education is actually character education. Discussions of eradicating corruption are often associated with providing the most severe criminal sanctions, often considered the most effective efforts. This view is in line with the use of criminal objectives developed in the classical school, namely absolute theory. The absolute theory was born in the classical school of criminal law. Based on this theory/school of thought, retaliation is the legitimacy of punishment. If related to this theory, eradicating corruption aims to take revenge against the perpetrators of corruption, and the form of retaliation is by imposing the most severe criminal sanctions on the corruptors. Keywords: Anti-Corruption Education, Anti-Corruption Value